MEASUREMENT OF THE FLOW IN CORONARY ARTERY BYPASS GRAFTS - Nemec, Petr; Bruk, Vilem; Steriovsky, Andrea; Gwozdzeiwicz, Marek; Hajek, Roman (Biomedical papers, 2006)
The aim of our study was to measure the flow in coronary artery bypass grafts and to compare the flow between two groups of patients. In group A the arterial revascularization was performed with both internal thoracic arteries using as a Y graft and in group B conventional revascularization using left internal thoracic artery (ITA) attached to the left anterior descending artery (LAD) and venous grafts to the other branches of the left coronary artery was performed. The flow in all grafts was measured at six time points during the operation. The cumulative flow at the end of the operation in the group A (arterial Y graft) was 51.8 extpm 24.5 ml/min and in group B (conventional technique) it was 96.8 extpm 41.1ml/min (p < 0.05). The flow in left ITA to LAD was similar in both groups (27.3 extpm 15.9 ml/min and 26.3 extpm 16.1 ml/min in group A and B). The flow in right ITA (25.2 extpm 18.4ml/min) was significantly lower than in venous grafts (72.5 extpm 45.5 ml/min). The calculated flow reserve was 2.2 in group A and 2.1 in group B. We found that the cumulative flow in arterial Y graft was lower in comparison with conventional revascularization. This is due to the lower flow in the right ITA branch of the Y graft compared to venous grafts. However based on clinical results, we can postulate that the flow in the Y graft is sufficient to meet the demand of the myocardium originally supplied by the left coronary artery.
Keywords: Coronary artery bypass/Flow measurement/Internal thoracic artery/Y graft